The Immunobiology of Tourette's Disorder, Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcus, and Related Disorders: A Way Forward - Murphy, Tanya K. (Mary Ann Liebert, Inc., 2010)
Obsessive-compulsive disorder (OCD) and related conditions including Tourette's disorder (TD) are chronic, relapsing disorders of unknown etiology associated with marked impairment and disability. Associated immune dysfunction has been reported and debated in the literature since the late 80s. The immunologic culprit receiving the most interest has been Group A Streptococcus (GAS), which began to receive attention as a potential cause of neuropsychiatric symptoms, following the investigation of the symptoms reported in Sydenham's chorea (SC) and rheumatic fever, such as motor tics, vocal tics, and both obsessive-compulsive and attention deficit/hyperactivity symptoms. Young children have been described as having a sudden onset of these neuropsychiatric symptoms temporally associated with GAS, but without supporting evidence of rheumatic fever. This presentation of OCD and tics has been termed pediatric autoimmune neuropsychiatric disorders associated with Streptococcus (PANDAS). Of note, SC, OCD, and TD often begin in early childhood and share common anatomic areas—the basal ganglia of the brain and the related cortical and thalamic sites—adding support to the possibility that these disorders might share a common immunologic and/or genetic vulnerability. Relevant manuscripts were identified through searches of the PsycINFO and MedLine databases using the following keywords: OCD, immune, PANDAS, Sydenham chorea, Tourette's disorder Group A Streptococcus. Articles were also identified through reference lists from research articles and other materials on childhood OCD, PANDAS, and TD between 1966 and December 2010. Considering the overlap of clinical and neuroanatomic findings among these disorders, this review explores evidence regarding the immunobiology as well as the relevant clinical and therapeutic aspects of TD, OCD, and PANDAS.